2022
DOI: 10.1371/journal.pone.0271717
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive accuracy and bias in somatic symptom disorder, illness anxiety disorder, and functional syndromes: A systematic review and meta-analysis

Abstract: Somatic symptom disorder, illness anxiety disorder, and functional syndromes are characterized by burdensome preoccupation with somatic symptoms. Etiological models propose either increased interoceptive accuracy through hypervigilance to the body, or decreased and biased interoception through top-down predictions about sensory events. This systematic review and meta-analysis summarizes findings of 68 studies examining interoceptive accuracy and 8 studies examining response biases in clinical or non-clinical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 163 publications
(159 reference statements)
1
12
0
1
Order By: Relevance
“…Recent research has emphasized differences in symptom perception in the different disorders. The findings are consistent with predictive coding theory, which highlights a decoupling of somatosensory input and the perception of body sensations 7 . For example, interoceptive inaccuracy appears to be a feature of the functional somatic syndromes, whereas a more liberal response bias has been observed in SSD 7 .…”
supporting
confidence: 86%
“…Recent research has emphasized differences in symptom perception in the different disorders. The findings are consistent with predictive coding theory, which highlights a decoupling of somatosensory input and the perception of body sensations 7 . For example, interoceptive inaccuracy appears to be a feature of the functional somatic syndromes, whereas a more liberal response bias has been observed in SSD 7 .…”
supporting
confidence: 86%
“…Indeed, a systematic review and a recent meta-analysis found no significant relation of interoceptive sensitivity and illness anxiety (56,57). Two studies drew clinical samples and did also not find higher sensitivity in patients suffering from PIA, neither in the tactile nor in the cardioceptive domain (34,58).…”
Section: Discussionmentioning
confidence: 99%
“…The brain hierarchically integrates sensory information (bottom-up input) and internal predictions about the expected information (top-down prior beliefs), each weighted according to their precision (mediated by top-down synaptic gain), to reach a posterior inference about what has happened (i.e., the percept). [160][161][162]213,221,[224][225][226][227][228][229][230] In Bayesian terms, this hierarchical process involves top-down prior predictions (represented by expectations), bottom-up likelihood (the Bayes Factor, represented by sensory input), and bottom-up prediction error (represented by the difference between the likelihood and prior, weighted by the precision of these two signals), to reach the posterior inference (represented by the percept) (see Figures 1 and 2). [160][161][162]213,221,[224][225][226][227][228][229][230] In this model, all experienced symptoms occur along a continuum of objectivity, more or less accurately representing what has happened to the body, and sometimes mistaking noise (normal bodily processes) for symptoms.…”
Section: Mechanisms Of Functional Disordersmentioning
confidence: 99%
“…[with] symptom report decoupled from sensory input." 230 Cardinal features of these amplified symptoms include disproportionate findings of physical distress (e.g., exceptionally noxious and disruptive symptoms, and multiplicity of symptoms), negative cognitions (e.g., "unnecessarily negative expectations, unduly alarming suspicions, troubling interpretations, worrisome beliefs about their significance and cause," including the conviction that an undiagnosed disease is present), health-related anxiety and disease fear, impairment of function (e.g., illness and sick-role behaviors, such as excessive use of medical care, information seeking, reassurance seeking, and avoidance of activity suspected of worsening symptoms), pervasiveness (e.g., preoccupied with symptoms that become part of self-identity), and dissatisfaction with medical care. 229 This unifying theoretical account strengthens the case that Long-COVID is usually a functional syndrome that was predictable given the common pandemic responses described below.…”
Section: How Bayesian Predictive Coding Can Lead To Perceptual Illusionsmentioning
confidence: 99%